Efeito neuroprotetor e antioxidante de Syzygium cumini (l.) Skeels e da miricetina na doença de parkinson em ratos - SILVA, Naíme Diane Sauaia Holanda (2020)
Parkinson's disease is currently considered the second most common neurodegenerative disease known as a disorder characterized mainly by its motor and cognitive symptoms. Syzygium cumini (L.) Skeels, popularly known as jambolão, is a native tree of northern and northeastern Brazil. Its leaves have high phenolic compounds and glycids. Miricetin, a phenolic compound present in the leaves of Syzygium cumini (L.) Skeels, has therapeutic properties such as antimicrobial, hypoglycemic and anti-inflammatory. In vitro evidence showed that both Syzygium cumini (L.) Skeels and Miricetin have low toxicity and antioxidant effects, suggesting potential therapeutic use. In the search for new therapies for PD, in this scenario arises the plant species and the phenolic compound with prospective therapeutic antioxidant and neuroprotective for systemic use. The aim of this study was to develop an herbal product derived from S. cumini leaves with antioxidant and neuroprotective activity applicable in Parkinson's disease. To investigate the effect of EHB, in vivo behavioral and antioxidant tests were performed with analysis of tissue samples (striatum, hippocampus and substantia nigra) by real time PCR. Treatment was performed daily in four groups of animals (n = 5; 90 days), randomly formed and treated concomitantly for two weeks as follows: negative control group (CTR) administered subcutaneous sunflower oil (sc) and solution 0.9% saline orally (vo) at doses of 0.1 ml / 100 g by weight; induced group: rats were induced with rotenone 2.5 mg / kg (s.c.) and saline (v.o); positive control group: rats given rotenone (s.c.) and miricetin 10 mg / kg (v.o.); induced groups treated with S. cumini plant extract: rats receiving rotenone (s.c.) and treated with S. cumini plant extract (EHB) at a dose of 500 mg / kg (v.o.). Regarding behavioral tests, the animals' weight decreased after induction of rotenone; In the open field test, the reduction in the quadrants traveled by the animals represents a decrease in exploratory activity and ambulation caused by rotenone-associated motor degeneration, that is, rotenone was successful in inducing Parkinson, but miricetin was not successful in reversing; In the rotarod test, the induced group had a decrease with an average of 2.86 ± 1.60 and the CTP group had a steeper decrease than in the induced group with an average of 2.00 ± 0.66. In the analysis of oxidative stress, rotenone administration increased Nrf2 gene expression, myricetin treatment was able to almost completely block the oxidation caused by rotenone, whereas in S.cumini EHB treatment in substantia nigra and hippocampus did not show significant expression compared to the group of miricetin, but in the striatum there was expression, but to a lesser extent than miricetin. He concluded that although the latest tests still need to be better explored we can have a possible herbal medicine for several dysfunctions associated with oxidative stress and neuronal preservation present in PD.